Multipotent mesenchymal stromal cells in otorhinolaryngology - Skoloudik, Lukas; Chrobok, Viktor; Kalfert, David; Koci, Zuzana; Filip, Stanislav (Medical hypotheses, 2014)
Multipotent mesenchymal stromal cells (MSCs) are primitive cells capable of restoring damaged mesenchyme and with the ability to differentiate into mature cells of bone, cartilage, muscle, fat, nerve or fibrous tissues. MSCs are therefore good candidates for applications in regenerative medicine and cell based therapy. They regenerate through self-renewal, differentiational capacity, immune modulation and secretion of bioactive molecules. Authors present a review of MSCs applications in otorhinolaryngology. The major interest is focused on phonosurgery, sensorineural deafness and reconstruction of large tissue defects with bone, cartilage or soft tissue replacement. Current evidence of MSCs treatment efficacy in otorhinolaryngology is based on animal models. The true impact on clinical treatment will not be known until clinical studies prove functional outcomes in human medicine.
Keywords: Animals; biologické modely; mezenchymální kmenové buňky; nervová tkáň; Cartilage; Guided Tissue Regeneration; kosti a kostní tkáň; buněčná diferenciace; lidé; Models, Biological; řízená tkáňová regenerace; transplantace mezenchymálních kmenových buněk; Mesenchymal Stem Cells; Regenerative Medicine; Mesenchymal Stem Cell Transplantation; Otolaryngology; chrupavka; otorinolaryngologie; Cell Differentiation; Nerve Tissue; zvířata; Bone and Bones; regenerativní lékařství; Humans